If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + 45 = 6b + 9 Reorder the terms: 45 + 5b = 6b + 9 Reorder the terms: 45 + 5b = 9 + 6b Solving 45 + 5b = 9 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 45 + 5b + -6b = 9 + 6b + -6b Combine like terms: 5b + -6b = -1b 45 + -1b = 9 + 6b + -6b Combine like terms: 6b + -6b = 0 45 + -1b = 9 + 0 45 + -1b = 9 Add '-45' to each side of the equation. 45 + -45 + -1b = 9 + -45 Combine like terms: 45 + -45 = 0 0 + -1b = 9 + -45 -1b = 9 + -45 Combine like terms: 9 + -45 = -36 -1b = -36 Divide each side by '-1'. b = 36 Simplifying b = 36
| 72+4-12d=3 | | 7a-2(-1)=17 | | 2(1+8n)+5n=17+6n | | 3m(m+9)= | | 4y-9=y+18 | | 2-0+3-7= | | 6x-5=3x+16 | | 8(12)+7= | | 6x+7-3x=2x+25 | | 6-(4-7a)=-2+8a | | 7x+-8=-28 | | 16(r+2)=60 | | 3r-5=20 | | 18*-5= | | 21+u=384+u | | 8xn=160 | | 6x+36=x+4(2x+3) | | 7(7c+-1)+-4c=82+c | | x-2=7-x | | X^3-4x^2+10x=0 | | 5x-(18-4x)=36 | | r+14=14 | | -16+26=-5(x+7) | | 6x+5-9x=13-18x+15x-8 | | X-8.8=-39 | | 67y^2-268=0 | | 2x(2x)-4x+2-8x(8x)-5= | | -7(5x-3y+4)= | | -3(7x-2)=29+2x | | cos(2x)=sin(30-x) | | 3z+b= | | 7x-6+3x-x-5= |